(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Bombax ceiba plant belongs to bombacaceae family and is commonly known as Semal (Hindi) and Cotton tree (English). It has numerous effects like stimulant, astringent, haemostatic, diuretics, antidiarrhoeal, emeticand antipyretic. Major pharmacological activities reported in this plant are hypoglycemic, antianxiety, antibacterial, antiviral and anti-inflammatory. Numerous side effects and increased resistance to anthelmintic drugs prompted us to discover cost effective safe formulation of conventional medicinal plants. In the present study, research work is focused to evaluate the possible anthelmintic effects of Bombax ceiba. To investigate anthelmintic potential of Bombax ceiba plant, different extracts from dried powder stem bark were tested on adult Indian earthworms (Pheretima posthuma) having physiological & anatomical resemblance with human intestinal roundworm parasites. The drugs were divided in 14 groups consisting of test, standard and control. Each group was consisting of six Indian earthworms of approximately same size. Albendazole was used as standard drug while tween80 in normal saline (1:1) was used as control. The result data reveals that all extracts have significant anthelmintic activity as compared to Albendazole taken as standard drug. The methanolic extract at dose of 50 mg/ml concentration showed paralysis time 30±0.96 minutes and death 33.66±0.71 minutes, which is equivalent to standard drug values at dose of 20 mg/ml. Ethylacetate extract at dose of 50 mg/ml showed paralysis at 28.66±0.71 minutes and death at 34.16±1.10 minutes, which proves that it is even better than standard drug in terms of paralysis time and equipotent in terms of time taken for causing death. Thus among the extracts, ethylacetate and methanolic extracts showed maximum activity with least time taken for paralysis and death of earthworms and were found equally potent as Albendazole at a dose of 50 mg/ml. Thus, Bombax ceiba traditional use in helminitic infestation was proved scientifically. On comparing phytochemical evaluation with anthelmintic activity it is assumed that glycosides may be responsible for this activity. A further investigation may lead development of novel anthelmintic drug or formulation with anthelmintic activity.